In triangle $ABC,$ the angle bisector of $\angle BAC$ meets $\overline{BC}$ at $D.$ If $\angle BAC = 60^\circ,$ $\angle ABC = 45^\circ,$ and $AD = 24,$ then find the area of triangle $ABC.$

Guest Mar 5, 2023

edited by
Guest
Mar 5, 2023

edited by Guest Mar 5, 2023

edited by Guest Mar 5, 2023

#1**+1 **

The third angle is 75 degrees (because sum of a triangle's angles is 180 degrees), then Law of Sines can be used to find the other sides. At that point, $A=\frac{1}{2}ab\sin(c)$ or Heron's formula could be used.

Guest Mar 5, 2023

#2**+1 **

First, let's draw a diagram:

Since the angle bisector of angle BAC meets BC at D, we know that AD bisects angle BAC. Therefore, angle BAD = angle CAD = 30 degrees.

Let's call the length of BC "x". Then we can use the Law of Sines to find the lengths of AB and AC:

sin(BAC) / AB = sin(ABC) / BC sin(60) / AB = sin(45) / x AB = (x * sin(60)) / sin(45) AB = x * sqrt(3)

sin(BAC) / AC = sin(ACB) / BC sin(60) / AC = sin(45) / x AC = (x * sin(60)) / sin(45) AC = x * sqrt(3)

Now we can use Heron's formula to find the area of triangle ABC:

s = (AB + BC + AC) / 2 s = (x * sqrt(3) + x + x * sqrt(3)) / 2 s = (2x * sqrt(3) + x) / 2 s = x * (sqrt(3) + 1) / 2 A = sqrt(s * (s - AB) * (s - AC) * (s - BC)) A = sqrt((x * (sqrt(3) + 1) / 2) * ((x * (sqrt(3) + 1) / 2) - (x * sqrt(3))) * ((x * (sqrt(3) + 1) / 2) - (x * sqrt(3))) * ((x * (sqrt(3) + 1) / 2) - x)) A = sqrt((x^2 * (sqrt(3) + 1)^2 / 4) * (3 / 4) * (3 / 4) * (1 / 4)) A = (3 * sqrt(3) * x^2) / 8

Therefore, the area of triangle ABC is (3 * sqrt(3) * x^2) / 8. We just need to plug in the value of x:

24 + x = BC x = BC - 24 AB = x * sqrt(3) = (BC - 24) * sqrt(3) AC = x * sqrt(3) = (BC - 24) * sqrt(3) s = x * (sqrt(3) + 1) / 2 s = ((BC - 24) * (sqrt(3) + 1) / 2) A = (3 * sqrt(3) * x^2) / 8 A = (3 * sqrt(3) * (BC - 24)^2) / 8 A = (3 * sqrt(3) * (BC^2 - 48BC + 576)) / 8 A = (9 * sqrt(3) * BC^2 - 108 * sqrt(3) * BC + 2592 * sqrt(3)) / 8 A =196*sqrt(3)

Therefore, the area of triangle ABC is 196*sqrt(3) square units.

Guest Mar 5, 2023

#5**+1 **

Yes, there is an error in the calculation of the area of triangle ABC. The value of x is correct, but the calculations for AB, AC, and s are incorrect.

We have:

AB = x * sqrt(3)

AC = (24 + x) * sqrt(3)

s = (BC + AB + AC) / 2 = (x + (24 + x) + (24 + x) * sqrt(3)) / 2

Substituting these values into Heron's formula, we get:

A = sqrt(s(s - AB)(s - AC)(s - BC))

= sqrt[((x + (24 + x) + (24 + x) * sqrt(3)) / 2) * (((24 + x) * sqrt(3)) / 2) * ((x + (24 + x) + (24 + x) * sqrt(3)) / 2 - x * sqrt(3)) * ((x + (24 + x) + (24 + x) * sqrt(3)) / 2 - (24 + x))]

= sqrt[(x + (24 + x) + (24 + x) * sqrt(3)) / 2 * (24 + x) * sqrt(3) / 2 * ((x + (24 + x) * sqrt(3)) / 2 - x * sqrt(3)) * ((x + (24 + x) * sqrt(3)) / 2 - (24 + x))]

= sqrt[(x + (24 + x) + (24 + x) * sqrt(3)) / 2 * (24 + x) * sqrt(3) / 2 * ((x * (sqrt(3) - 1) + 12 + 12 * sqrt(3)) / 2) * (((24 + x) * (sqrt(3) - 1) + 12 + 12 * sqrt(3)) / 2)]

= sqrt[(x + (24 + x) + (24 + x) * sqrt(3)) / 2 * (24 + x) * sqrt(3) / 2 * ((x * sqrt(3) + 36) / 2) * (((24 + x) * sqrt(3) + 36) / 2)]

= sqrt[(x^2 + 48x + 576) * 27 / 4]

= sqrt[27(x^2 + 48x + 576) / 4]

= sqrt[27((x + 24)^2 - 144) / 4]

= sqrt[27(x + 24)^2 / 4 - 27 * 36]

= sqrt[27/4 * (x + 24)^2 - 972]

Now, substituting the value of x = 24, we get:

A = sqrt[27/4 * (24 + 24)^2 - 972]

= sqrt[27/4 * 48^2 - 972]

= sqrt[27 * 12^2 - 972]

= sqrt[2916]

= 54

Therefore, the area of triangle ABC is 54 square units.

Justingavriel1233
Mar 5, 2023

#7**+1 **

We can start by using the angle bisector theorem to find the lengths of the sides of triangle ABC. Let E be the point on AB where the angle bisector of angle BAC intersects AB. Then, we have:

BD/DC = AB/AC

Since angle ABC = 45 degrees, we know that AB = BC, so we can substitute:

BD/DC = AB/AC = BC/AC

Since angle BAC = 60 degrees, we know that angles ABC and ACB are each 60/2 = 30 degrees. Using the sine rule, we can find AC:

AC/sin(30) = BC/sin(60)

AC = 2BC

Substituting this into the angle bisector theorem, we have:

BD/DC = BC/(2BC) = 1/2

So, BD = BC/3 and DC = 2BC/3.

Now, let's use the fact that the area of a triangle is 1/2 times the base times the height. We can use AD as the height, since it is perpendicular to BC, and we can use BC as the base. To find the length of BC, we can use the Pythagorean theorem on triangle ABC:

AB^2 + BC^2 = AC^2 BC^2 + BC^2 = (2BC)^2 2BC^2 = 4BC^2 BC^2 = 2AC^2 BC = AC/sqrt(2)

Now we can find the area of triangle ABC:

Area = 1/2 * BC * AD = 1/2 * (AC/sqrt(2)) * 24 = 12 * AC/sqrt(2) = 12AC * sqrt(2)/2 = 6AC * sqrt(2)

To find AC, we can use the sine rule on triangle ABC:

AC/sin(60) = BC/sin(45) AC = BC * sqrt(3)/2

Substituting this into the area formula, we have:

Area = 6AC * sqrt(2) = 6 * BC * sqrt(3)/2 * sqrt(2) = 3BC * sqrt(6)

Finally, we can use the Pythagorean theorem again to find BC:

AB^2 + BC^2 = AC^2

So, BC = 20*sqrt(2)

Substituting this into the area formula, we have:

Area = 3BC * sqrt(6) = 60*sqrt(6)

Therefore, the area of triangle ABC is 60*sqrt(6).

Guest Mar 5, 2023

#9**+1 **

Here are the steps to the solution:

1)Draw the triangle.

2) Mark in all the angles. You have enough information to find the whole lot just using the angle sum of a triangle.

3) Now just by looking at what kind of triangles you have and you can see the length of AC

4) Use sin rule to find BC [AC would be ok too but it is easier to get an exact area using BC]

5) Now you have all the angles and 2 sides so use the formula to find the area of ABC. ( area= 0.5xysinZ, if it had beeen triangle XYZ)

My answer is different from all the others but I could easily have made a careless error.

If you are really interested in learning then follow my instructions and see where it takes you.

You can ask questions along the way if you want to.

Melody Mar 7, 2023